Design, konstruktion och utvärdering av en optisk förstärkare - Hult, Björn; Johannesson, Henric; Vikstål, Pontus; Wall, Arvid (My University, 2016)
Erbium-doped fiber amplifiers are most commonly used in fiber-optic communication systems to amplilfy optical signals. A pump laser is joined together with erbium-doped fiber to excite the erbium ions inside the erbiumdoped fiber so that the attenuated optical signal later can be amplified by stimulated emission. This report treats the construction of a forward pumping erbium-doped fiber amplifier and a two-step erbium-doped amplifier. The forward pumping amplifier uses a 980 nm pump laser with a pump power at 123 mW and the two-step amplifier is a combination between a forward pumping and a backward pumping amplifier. In the two-step amplifier the forward pumping part uses a 123 mW, 980 nanometer laser and the backward pumping part uses a 251 mW, 1480 nm laser. A gain at 29.4 dB and a noise figure at 6.6 dB was achived for the forward pumping amplifier, with an optimal erbiumfiber length that was experimentally found to be 29 meters. These values vary widely from the theoretical modell that was applied as a tool for the forward pumping amplifier to help us predict the parameters that would result in highest gain and lowest noise figure. The values from the computer simulations for the forward pumping amplifier gave a gain at 34.11 dB and a noise figure at 6.4, which quite well satisfy the experimentally measured values. The forward pumping erbium-doped amplifier can be compared with commercially produced amplifiers [1] that has a gain over 30 dB and a noise figure under 4.3 dB. For the dual-stage amplifier a gain at 50.1 dB and a noise figure at 5.6 dB was achived. The second stage of the dual-stage amplifier can be compared with other commercially available amplifiers [1] that has a gain bigger than 19 dB. The measurment tools that were used in the measurments were an optical spectral analyzer and an optical power meter.
Keywords: Fotonik; Informations- och kommunikationsteknik; Photonics; Information & Communication Technology